Writing Anxiety among EFL Students of John Senior High School - Alvian Adhi Nugroho; Ouda Teda Ena (Institut Agama Islam Negeri Palopo, 2021)
The objective of this is to examine the level of deep writing anxiety experienced by high school students in learning English as a foreign language for various reasons and consequences of the anxiety. Many results of research on scientific papers in this decade indicate that writing anxiety in foreign languages has negative effects on attitudes, success, student achievement, hinders the writing process, and reduces interest in writing. In this study, the quantitative research method is used to measure the level of anxiety experienced by students. This study adapted the Second Language Writing Anxiety Inventory questionnaire compiled by (Cheng, 2004). The results showed that the participants had high and moderate writing anxiety. Cognitive anxiety showed the highest result. Whereas, avoidance anxiety was reported in the second position of writing anxiety. The lowest score was performed by somatic anxiety that occurred in the result. They have problems in choosing a topic to write on, finding helpful ideas, time constraints, and a lack of effective feedback are the most worrying factors, followed by grammar, brainstorming, idea organization, and topic sentence writing.